Levels of satisfaction with children's respite services, parental coping and family functioning. (4th November 2019) - McKiernan, Aidan; Carr, Alan; O'Keeffe, Lynsey; Butler, Ellen; Quinn, Claire; Guerin, Suzanne
Abstract: Little is known about how parents' experiences of respite services or 'short breaks' for a child with complex medical needs relate to family functioning and the manner in which parents cope. The aim of this study was to examine the relationship between parents' satisfaction with short breaks, family functioning and parental coping and to determine whether these variables change over time. The sample included 32 families receiving short breaks. A repeated measures quantitative design was used, with data collected at baseline and 12 months. The main outcome variables were satisfaction with short breaks, family functioning and parental coping. At baseline, descriptive statistics showed positive levels of satisfaction with services and coping, while family functioning scores suggested more negative profiles. Also at baseline, significant negative correlations were identified between the age of the child receiving short breaks and certain approaches to parental coping. At Time 2 ( n  = 17, 73% of possible responses), satisfaction with services was significantly positively correlated with aspects of family functioning and coping. Using dependent t tests, no evidence was found of significant change overtime in satisfaction or family functioning for the sample who completed data collection at both time points. However, a significant decrease in use of certain coping approaches was found over time. While parents' satisfaction levels with short breaks were high across test occasions, there is need for service development aimed at providing interventions that are tailored to ameliorate tension within the family and promote active parental coping over time.